Modeling of the General Trends of Reactivity and Regioselectivity in Cyclopentadiene–Nitroalkene Diels–Alder Reactions - Adrianna Fałowska; Stanisław Grzybowski; Daniel Kapuściński; Karol Sambora; Agnieszka Łapczuk (Molecules)
This study presents a theoretical investigation of the electronic properties of mono- and pentasubstituted cyclopentadiene analogs and variously substituted conjugated nitroalkenes bearing electron-donating and electron-withdrawing groups. Conceptual Density Functional Theory (CDFT) and Electron Localization Function (ELF) analyses were employed to characterize the global and local reactivity indices of the reactants. The obtained data provided insights into the nucleophilic and electrophilic nature of the investigated systems, allowing for the prediction of their reactivity patterns in Diels–Alder reactions. A reactivity model for conjugated alkenes toward cyclopentadienes was developed based on correlation analysis using Hammett substituent constants. This approach enabled the prediction of reaction polarity in (4+2) cycloaddition processes, providing insight into how the electronic effects of substituents influence the reaction course. These findings contribute to a deeper understanding of structure–reactivity relationships in Diels–Alder processes.